Effect of intranasal steroids on rhinosinusitis after radiotherapy for nasopharyngeal carcinoma: clinical study. Issue 3 (7th January 2016) - Feng, S; Fan, Y; Liang, Z; Yang, G; Liao, Z; Guo, L
Abstract: Objective: Post-irradiation rhinosinusitis is one of the most common untoward side effects in patients with nasopharyngeal carcinoma. This study aimed to evaluate the effect of fluticasone propionate aqueous nasal spray on post-irradiation rhinosinusitis. Methods: Nasopharyngeal carcinoma patients who had undergone radiotherapy and subsequently developed chronic rhinosinusitis were randomised to receive either fluticasone propionate aqueous nasal spray 200 µg plus nasal irrigation or a single nasal irrigation, for six months. A questionnaire, nasal endoscopy and computed tomography were used to evaluate rhinosinusitis severity, at the beginning of treatment, and at three and six months after treatment. Results: The group who received fluticasone propionate aqueous nasal spray combined with irrigation had fewer nasal complaints (overall symptoms, blocked nose and headache were reduced), a better quality of life and less severe endoscopic findings than those who only received nasal irrigation at three and six months after treatment. Conclusion: Nasal steroids are a safe and effective therapy for patients with post-irradiation rhinosinusitis.